Evaluation of PET/MRI for Tumor Volume Delineation for Head and Neck Cancer - Wang, Kyle; Mullins, Brandon T.; Falchook, Aaron D.; Lian, Jun; He, Kelei; Shen, Dinggang; Dance, Michael; Lin, Weili; Sills, Tiffany M.; Das, Shiva K.; Huang, Benjamin Y.; Chera, Bhishamjit S. (Frontiers in Oncology, 2017)
Introduction CT, PET/CT, and MRI are commonly used in head and neck radiation planning. Hybrid PET/MRI has garnered attention for potential added value in cancer staging and treatment planning. We herein compare PET/MRI vs. planning CT for head and neck cancer gross tumor volume (GTV) delineation. Material and Methods We prospectively enrolled patients with head and neck cancer treated with definitive chemoradiation to 60-70 Gy using IMRT. We performed pre-treatment contrast-enhanced planning CT and gadolinium-enhanced PET/MRI. Primary and nodal volumes were delineated on planning CT (GTV-CT) prospectively before treatment and PET/MRI (GTV-PET/MRI) retrospectively after treatment. GTV-PET/MRI was compared to GTV-CT using separate rigid registrations for each tumor volume. The Dice similarity coefficient (DSC) metric evaluating spatial overlap and modified Hausdorff distance (mHD) evaluating mean orthogonal distance difference were calculated. Minimum dose to 95% of GTVs (D95) was compared. Results 11 patients were evaluable (10 oropharynx, 1 larynx). 9 patients had evaluable primary tumor GTVs and 7 patients had evaluable nodal GTVs. Mean primary GTV-CT and GTV-PET/MRI size were 13.2cc and 14.3cc, with mean intersection 8.7cc, DSC 0.63, and mHD 1.6mm. D95 was 65.3Gy for primary GTV-CT vs. 65.2Gy for primary GTV-PET/MRI. Mean nodal GTV-CT and GTV-PET/MRI size were 19.0cc and 23.0cc, with mean intersection 14.4cc, DSC 0.69, and mHD 2.3mm. D95 was 62.3Gy for both nodal GTV-CT and GTV-PET/MRI. Conclusion In this series of patients with head and neck (primarily oropharynx) cancer, PET/MRI and CT GTVs had similar volumes (though there were individual cases with larger differences) with overall small discrepancies in spatial overlap, small mean orthogonal distance differences, and similar radiation doses.